Efektivitas Metode Mengaji Ummi Terhadap Kemampuan Membaca Al-Qur’an Siswa Kelas 5 Madrasah Ibtidaiyah Negeri 1 Jombang - Muhtadi Muhtadi; Imam Mashudi Latif; Muhammad Chafi Asadal Haq (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
This study aims to determine the effectiveness of the Ummi Quran reading method on the ability to read the Qur'an of grade 5 students of MIN 1 Jombang. This type of research is quantitative research with a correlative approach. The data collection method is observation, interview, questionnaire and documentation. While the data analysis uses a statistical method with the product moment correlation formula. The results of the study indicate that based on the product moment correlation analysis, the effectiveness of the Ummi Quran reading method has a correlation with the ability to read the Qur'an of grade 5 students with a correlation index (rxy) = 0.663 and is interpreted at a significant level of 5% = 0.2787, while at a level of 1% = 0.3610. Which means that rxy is greater than the significant level, then the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. So it can be concluded that there is a positive correlation between the Effectiveness of the Ummi Quran Reading Method on the Ability to Read the Qur'an of Grade 5 Students of MIN 1 Jombang. Keywords: Ummi Method; Ability to Read the Qur'an